Types Of Apathetic Behaviour In Jersey Girl (2004) Movie Script By Kevin Smith - Febrika Vivience Paratte; Sudirman Maca; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2025)
The research employed Sigmund Freud’s psychoanalysis and Kuravati & Malipati theory, and Ang & Lockwood’s classification of apathy to analyse the apathetic behaviour of the main character in Jersey Girl (2004) by Kevin Smith. The purpose of the study is to determine the types of apathetic behaviour, their causal factors, and their effects on the main character’s interactions. The research is descriptive qualitative, and the data source is the script of the 2004 film Jersey Girl. The findings reveal that three categories of apathetic behaviour: eight data of social apathy, three data of behavioural apathy, and two data of emotional apathy. Profound grief due to job loss and the death of a spouse were identified as the main cause of apathy. Based on Freud’s psychoanalytical analysis, two personality components influence apathy behaviour: the ego (12 data) and the id (1 data), the ego being the most dominant. Apathetic behaviour affects the main character in several ways, including decreased social interest, reduced motivation, difficulty in building new relationships, and loss of emotional control. It was expected that the study in which, particularly character analysis is appropriate through psychoanalytic approach.